PROGRAM PEMBERDAYAAN PEREMPUAN KEPALA KELUARGA UNTUK MENGATASI KEMISKINAN DAN MENCAPAI TUJUAN SUSTAINABLE DEVELOPMENT GOALS DI INDONESIA : ANALISIS BIBLIOMETRIK - Serly Wulandari; Ika Sartika (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2025)
Poverty is still a major problem that has not been completely resolved. Therefore, SDGs are present as a global and national commitment to realize sustainable development globally and improve people's welfare. The first goal of SDGs is no poverty, with one of the empowerment programs called Women Heads of Households. This study aims to analyze issues related to the empowerment program for women heads of households using literature studies from the Scopus database, and describe the findings on 1) developments in publication trends, 2) the most influential researchers and articles, 3) article linkage maps seen from the co-occurrence of author keywords. The author uses bibliometric analysis processed using the publish or perish and Vosviewer applications. The results of the analysis show that the topic has begun to receive research attention since 1988 with the highest number of publications occurring in 2020 as many as 72 articles. The article entitled Global Burden of Cardiovascular Diseases and Risk Factors, 1990-2019: Update From the GBD 2019 Study written by G.A. Roth received the highest number of citations of 5917 citations. As for the analysis of the article seen from the co-occurrence relationship map of the author's keywords, 17 (seventeen) clusters were formed. Issues related to equality are one of the most frequent and long-discussed topics in research related to the empowerment program for women heads of families.